Strategi Marketing Mix untuk Meningkatkan Minat Nasabah pada Produk Funding - Muh Hamzah; Farisa Irwayu (JURNAL PROFIT, 2023)
Marketing strategy is one way to win a sustainable competitive advantage for a company. The marketing strategy can be viewed as one of the bases used in preparing the overall company plan. The purpose of this study was to determine the application of the marketing mix strategy in increasing the percentage of customer interest in funding products at BSI KCP Situbondo A. Yani. This study uses a qualitative method with a descriptive approach. Data collection is done through observation, interviews and documentation or reports by describing the object of the research. The results and research are elements of the marketing mix consisting of product, price, place process, promotion, people and physical evidence carried out by BSI KCP Situbondo A. Yani is quite good. Based on the results of the first study, BSI KCP Situbondo A Yani has implemented the 7P marketing mix strategy well. Second, the amount of funding at BSI KCP Situbondo A Yani will increase in 2022 after experiencing a significant decline from 2020 to 2021 during the Covid-19 pandemic. And thirdly, there is an increase in the number of customers who are interested in using funding, lending products and increasing income every month. The application of the marketing mix in increasing the percentage of customer interest in funding products carried out by BSI KCP Situbondo A. Yani is quite effective because there is an improvement in the number of customers from time by time.